História de Vida: Uma Oportunidade Não Explorada em Pesquisas de Marketing (Management and Connections Journal, 2022)
Life history is a means of qualitative research that seeks to understand life as it is reported/interpreted by the subject, who performs a reflection on his/her life. Its ability to uncover aspects of the human experience, and of understanding how people interact, interpret and construct their meanings, can be very useful in consumer behavior studies. This article checks the purpose of the Brazilian Administration research from the last ten years in the SPELL database that has used life history as a means of research, in order to find out to what extent their authors followed the suggestion of turning their attention to the Marketing field, specifically in the consumer behavior area. Having found a lack of interest for this investigative path, assumptions about it are proposed, as well as suggestions for mitigating this gap.